Synergistic hydroxyl radical formation, system XC- inhibition and heat shock protein crosslinking tango in ferrotherapy: A prove-of-concept study of "sword and shield" theory. (December 2022) - Xie, Li; Chen, Wenjie; Chen, Qifang; Jiang, Yang; Song, Erqun; Zhu, Xiaokang; Song, Yang
Abstract: Ferroptosis provide new insights into designing nanomedicines for enhanced cancer therapy; however, its antitumor efficacy is relatively low, mainly due to self-protective mechanism of cancer cells, e.g., heat shock protein (HSP) overexpression. Since HSPs can be modified/inhibited by lipid peroxidation (LPO) ending products, we construct a nanoplatform, namely MPDA@Fe3 O4 -Era, to amplify intracellular reactive oxygen species (ROS) and LPO for synergistic ferrotherapy. Upon tumor acidic microenvironment and local near-infrared stimuli, this nanoplatform releases Fe3 O4 and reacts with intracellular hydrogen peroxide (H2 O2 ) to promote Fenton reaction, and yields significant intracellular ROS (specifically hydroxyl radical, OH) and LPO. In turn, LPO ending products crosslink HSPs to destroy self-preservation pathways of cancer cells to enhance anticancer effect. Meanwhile, the released erastin inhibits system XC − signal pathway to depletes glutathione. Fe3 O4 loading further provides magnetic resonance imaging T2-weighted signal to guide anti-tumor treatment. Together, this nanoplatform not only provides OH (as a "sword" to attack tumor cells), but also inhibits system XC − signal pathway and crosslinks HSP (break down the "shield" of tumor cells) to maximize synergistic ferro-therapeutic effect. MPDA@Fe3 O4 -Era plus laser irradiation possessed highly efficient tumor suppression with magnified the levels of OH and inactive glutathione peroxidase 4 (GPX4), which can promote the development of precise cooperative cancer therapy. Graphical abstract: Image 1